2004
DOI: 10.1109/tnb.2004.828268
|View full text |Cite
|
Sign up to set email alerts
|

A Parallel-Plate Flow Chamber to Study Initial Cell Adhesion on a Nanofeatured Surface

Abstract: Abstract-Cells in the human body come across many types of information, which they respond to. Both material chemistry and topography of the surface where they adhere have an effect on cell shape, proliferation, migration, and gene expression. It is possible to create surfaces with topography at the nanometric scale to allow observation of cell-topography interactions. Previous work has shown that 100-nm-diameter pits on a 300-nm pitch can have a marked effect in reducing the adhesion of rat fibroblasts in sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…Mechanisms underpinning attachment to nanoscale topographies for mammalian cells is a greatly studied area which has continued to foster significant findings and major contributions to the wealth of knowledge on eukaryotic cell behavior [82][83][84][85]. However, as Hsu et al [48] have described, attachment phenomena for bacterial cells at the nanoscale is less understood, as relatively few reported works have explored the effects of nanoscale topography on bacterial attachment behavior and biofilm formation [23,49,54,86,87].…”
Section: Pushing Antifouling Topography To the Nanoscalementioning
confidence: 99%
“…Mechanisms underpinning attachment to nanoscale topographies for mammalian cells is a greatly studied area which has continued to foster significant findings and major contributions to the wealth of knowledge on eukaryotic cell behavior [82][83][84][85]. However, as Hsu et al [48] have described, attachment phenomena for bacterial cells at the nanoscale is less understood, as relatively few reported works have explored the effects of nanoscale topography on bacterial attachment behavior and biofilm formation [23,49,54,86,87].…”
Section: Pushing Antifouling Topography To the Nanoscalementioning
confidence: 99%
“…Since osteoblast adhesion occurred preferentially at surface particle boundaries and more of them are present on the nanophase compared to conventional material, this may explain the observed increase in osteoblast adhesion [Webster and Ejiofor, 2004]. However, this phenomenon may be cell specifi c, since reduced fi broblast adhesion was observed on nanosized pits (PMMA, 35-120 nm in diameter) Martines et al, 2004]. We observed well-formed focal contacts by fl uorescence labeling for vinculin only at later time points (6 and 24 h), but not during the fi rst 90 min of cell adhesion.…”
Section: Surface Composition and Cell Adhesionmentioning
confidence: 99%
“…Now, Teixeira et al [2003] found that corneal epithelial cells elongate and align along silicone ridges 70 nm wide and 150 nm deep. Reduced fi broblast adhesion was observed using nanosized pits on polymethylmethacrylate (PMMA, 35-120 nm in diameter, pitch 100-300 nm) Martines et al, 2004]. On 13-nm-high islands produced by demixing of polymers, fi broblasts showed increased cell spreading and upregulation of gene expression [Dalby et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] A microfluidic system is advantageous for analysis of cell adhesion in various aspects because of small sample consumption, use of multiple parameters, and generation of large shear stress. 26,27 By integrating nanostructured surfaces with a microfluidic system, we herein devise a simple, label-free cell separation and enrichment scheme based on standard soft lithography and microfluidics protocol. The PDMS microfluidic device consists of four branch channels, each of which contains flat or polymeric nanostructures on the bottom (400 nm pillars, 400 nm perpendicular, and 400 nm parallel lines, respectively) to increase the difference in cell adhesion.…”
Section: Introductionmentioning
confidence: 99%